Dry reforming of methane over Ɣ-Al2O3 supported NiCo and NiCoCu nano-catalysts. Issue 3 (19th February 2023) - Ghanbarabadi, Hassan; Khoshandam, Behnam
ABSTRACT: In the present study, Ni-Co, Ni-Cu bimetallic nanocatalyst (BMNC), and Ni-Co-Cu trimetallic nanocatalyst (TMNC) were synthesized on the γ − A l 2 O 3 base using the thermogravimetric method. The thermogravimetric method is a pyrometallurgical route (TGPR). These nanocatalysts were produced from the reduction reaction of binary and ternary mixture of NiO, Co3 O4, and CuO metal oxide nanoparticles (NPs), along with a γ − A l 2 O 3 base with methane gas. The reduction reaction was carried out at 830°C with 23vol.% of methane as a reducing agent under atmospheric pressure. The properties of N i C o / γ − A l 2 O 3 BMNC and N i C o C u / γ − A l 2 O 3 TMNC were analysed by XRD, FESEM, TPO, and BET and then their the nanocatalysts' performance was evaluated with dry reforming of methane (DRM). The XRD results indicated that in the production of NPs-C, the utilised metal oxides were converted into metal NPs, which created bi- and tri-metallic bonding with the γ − A l 2 O 3 base. BET analysis demonstrated that the surface area and pores volume of the TMNC reduced as the primary CuO particles entered the pores, due to the smaller average size of these particles in comparison to nickel and cobalt oxide NPs. In addition, the catalytic results revealed that N i C o / γ − A l 2 O 3 BMNC has the highest catalytic performance compared to N i C o C u / γ − A l 2 O 3 TMNC, due to the absence of CuO and the appropriate synergistic effect of nickel-cobalt in the DRM. The TPO analysis confirmed the decrease in the amount of carbon sediment in the TMNC, resulted from the presence of Cu.